The effects of gamification on learning-transfer of critical thinking dispositions among teachers - Aldarbi, Amjad J. S (Kulliyyah of Education, 2020)
Teaching critical thinking, while important and essential especially in the 21st century, has been facing documented shortcomings and overall inadequateness. In the meanwhile, gamification as a pedagogical strategy has been reporting encouraging results in the field of education. Thusly, this current study was set to test possible gamification effects on learning transfer of one component of critical thinking, that is critical thinking dispositions. Sixty-eight teachers from Saudi Arabia were engaged in a true-experiment training course for a week. Three dimensions of learning transfer were adapted from the Learning Transfer System Inventory (LTSI) to be used as a post-test. The results from the independent samples t-test, performed to compare the treatment group with the control group, showed that gamification had no significant effect on the three learning transfer dimensions, namely: motivation to transfer, transfer design, and perceived content validity. The study ends with practical implications as contributions to the field, along with recommendations for future research in gamified education and recommendations for educators.